A review of the millipede genus Rupidesmus Schubart, 1952 (Polydesmida: Chelodesmidae) - Bouzan, Rodrigo Salvador; Iniesta, Luiz Felipe M.; Brescovit, Antonio Domingos (Zootaxa, 2018)
The chelodesmid genus Rupidesmus Schubart, 1952 is revised. Currently, the genus contains only Rupidesmus ruber Schubart, 1952, herein redescribed, and the new species Rupidesmus aclys n. sp., added. A revised diagnosis for the genus and a distribution map for the two species are provided.